THE DYNAMIC INTERPLAY OF TRADITION, IMAGE, AND SYMBOL IN SHAPING CULTURAL IDENTITY - Ubaydullayeva Sadoqat Sobirjon Qizi; Abduraimova Shabnam Zokirjon Qizi; Eshbo’riyeva Husnora Azamat Qizi (TADQIQOTLAR, 2025)
Abstract Traditions, images, and symbols are cornerstones of cultural identity, serving as conduits for preserving heritage, expressing values, and fostering community cohesion. This study investigates their interconnected roles through a qualitative analysis of diverse cultural practices, including rituals, visual arts, and symbolic artifacts. By examining case studies from Japanese, Native American, Islamic, and Indian cultures, we explore how traditions provide continuity, images convey narratives, and symbols encapsulate complex meanings.